Childhood and education in the United States and Russia : sociological and comparative perspectives - Bodovski, Katerina (Emerald Publishing Limited, 2019)
Current tensions between the U.S. and Russia are at their highest since the end of the Cold War. In such circumstances, it is imperative to go beyond headlines and rhetoric and take a closer look at the texture of Russian and American societies. Childhood and Education in the United States and Russia provides a rich illustration of the social processes within these countries. Through an extensive interdisciplinary literature review and quantitative analyses of both national and international datasets, this book sheds light on three main areas. Firstly, it explores the extent to which the institution of education intersects with the institution of childhood in Russia and the U.S. Secondly, the author provides an illuminating study of how childhood is stratified by the social background into which a child is born in Russia and the U.S. Finally, this book gives new insight into how we observe the strengthening of children's agency, both in theoretical developments in sociology of education and childhood, and educational practice and parental strategies. By discussing education and childhood from a sociological perspective with a focus on similarities and differences by time and place, this book will prove an invaluable resource for students and researchers in the fields of Sociology of Education, Sociology of Childhood and International Education.